2022
DOI: 10.1111/bph.15850
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of endothelial dysfunction by sodium glucose co‐transporter 2 inhibitors: pieces of the puzzle explaining their cardiovascular protection

Abstract: Sodium glucose co-transporter 2 inhibitors (SGLT-2is) improve cardiovascular outcomes in both diabetic and non-diabetic patients. Preclinical studies suggest that SGLT-2is directly affect endothelial function in a glucose-independent manner. The effects of SGLT-2is include decreased oxidative stress and inflammatory reactions in endothelial cells. Furthermore, SGLT2is restore endothelium-related vasodilation and regulate angiogenesis. The favourable cardiovascular effects of SGLT-2is could be mediated via a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 93 publications
0
14
0
1
Order By: Relevance
“…Therefore, besides inducing a low-grade ketonemia, empagliflozin might be associated with broader, additional pleiotropic effects independent of BOHB. It has been suggested that SGLT2 inhibition may lead to a greater benefit by augmenting endothelial function and vasodilatation, 3,12,26 improvements in nutrient deprivation signaling/autophagy 27 or tapping the native response of tissues to ischemia (hypoxia-inducible factor). 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, besides inducing a low-grade ketonemia, empagliflozin might be associated with broader, additional pleiotropic effects independent of BOHB. It has been suggested that SGLT2 inhibition may lead to a greater benefit by augmenting endothelial function and vasodilatation, 3,12,26 improvements in nutrient deprivation signaling/autophagy 27 or tapping the native response of tissues to ischemia (hypoxia-inducible factor). 28…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, besides inducing a low-grade ketonemia, empagliflozin might be associated with broader, additional pleiotropic effects independent of BOHB. It has been suggested that SGLT2 inhibition may lead to a greater benefit by augmenting endothelial function and vasodilatation, 3,12,26 improvements in nutrient deprivation signaling/autophagy 27 or tapping the native response of tissues to ischemia (hypoxia-inducible factor). 28 One-week duration of treatment before MI was selected based on previous experimental studies with rodents showing the critical importance of timing and duration of treatment when it applies to cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of SGLT2i in improving cardiovascular complications was found to be independent of the hypoglycemic effect. 22 The pharmacological mechanisms by which SGLT2i exert cardioprotective effects include improving hemodynamics through blood pressure/volume reduction and inhibiting PVAT remodeling 23 ; inhibiting glucose oxidation, increasing fat oxidation, and raising plasma ketone body levels to improve cardiac energy efficiency 24 ; improving endothelial function and vascular stiffness by anti-inflammatory and antioxidant effects 25 , 26 ; and inhibiting myocardial Na + /H + exchange (NHE), reducing intracellular Na + and Ca 2+ concentrations in cardiomyocytes, and enhancing resistance to oxidative stress. 27 Owing to its prominent and significant cardiovascular protective effect, guidelines in many countries recommend its use in nondiabetic patients with heart failure.…”
Section: Overview Of Sglt2imentioning
confidence: 99%
“…Существует несколько возможностей косвенного фармакологического влияния на эти процессы с помощью препаратов, которые уже успешно применяются для лечения СН (ингибиторы АПФ и блокаторы ангиотензиновых рецепторов, валсартан/сакубитрил и ингибиторы SGLT2) [58][59][60][61][62], а также атеросклероза (статины) [63]. Что касается заместительной терапии в форме применения нитратов и донаторов NO, то их положительное влияние на гемодинамику, ремоделирование, а в некоторых группах пациентов (у афроамериканцев с тяжелой СН) -на выживаемость [58,64] обычно с течением времени нивелируется в результате возникновения побочных эффектов (чаще артериальной гипотензии), толерантности и оксидативного стресса.…”
Section: влияние No и эндотелиальной дисфункции на течение сн и возмо...unclassified